Pengukuran dan Validasi Skala Self Awareness - Ukti Julmi Putri; Frischa Meivilona Yendi; Febri Wandha Putra; Yarmis Syukur (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2026)
This study aims to examine the validity and reliability of the self-awareness scale among Indonesia Smart Card (KIP) recipient students at Universitas Negeri Padang. Self-awareness is defined as a physical and psychological process that influences mental life, related to life goals, emotions, and cognition. This research uses a quantitative method with descriptive and correlational approaches. The population of the study consists of 35 KIP recipient students selected using total sampling technique. The research instrument is a Likert scale questionnaire with 37 items, formulated based on Solso’s (2007) indicators. The validity test using Pearson Product Moment correlation shows that 28 out of 37 items are valid. The reliability test yields a Cronbach's Alpha value of 0.900, indicating excellent reliability. The results of this study support the use of this instrument to measure self-awareness among KIP recipient students and indicate that self-awareness plays a crucial role in student learning and personal development.